A novel method of optimizing patient- and family-centered care in the ICU. Issue 3 (March 2017) - Allen, Steven R.; Pascual, Jose; Martin, Niels; Reilly, Patrick; Luckianow, Gina; Datner, Elizabeth; Davis, Kimberly A.; Kaplan, Lewis J.
Abstract : BACKGROUND: Patient- and family-centered care permeates critical care where there are often multiple teams involved in management. A method of facilitating information sharing to support shared decision making is essential in appropriately rendering care. This study sought to determine whether incorporating family members on rounds in the intensive care unit (ICU) improves patient and family knowledge and whether doing so improves team time management and satisfaction with the process. METHODS: A nonrandomized comparative before-and-after trial of incorporating family members on rounds (July to December 2009 vs January to July 2010) in a single quarternary center's surgical ICU assessed (1) family members' knowledge, (2) nurse's and physician's satisfaction with the intervention, (3) frequency and timing of family meetings, and (4) physician's workflow. RESULTS: Intensive care unit demographics and use were similar between time frames. Presurvey (n = 412 family members; 49 nurses) and postsurvey (n = 427 family members; 47 nurses) were coupled with presurvey (n = 5) and postsurvey (n = 6) physicians' informal feedback. Family knowledge of the clinical course and plans increased from 146 (35.4%) of 412 to 374 (87.6%) of 427 ( p < 0.0001). Nurses were nearly uniformly satisfied with planned family interaction on rounds (presurvey: 9/49 [18.4%] vs postsurvey: 46/47 [97.9%]; p < 0.0001). Family meetings per week outside of rounds substantially decreased from a mean of 5.3 ± 2.7 to 0.3 ± 0.9; p < 0.001). Goals of therapy including end-of-life care became an element frequently discussed on rounds with families (presurvey: 9.4% ± 4.7% vs postsurvey: 82.5% ± 14.8%; p < 0.0001). One intensivist was dissatisfied with the process. CONCLUSION: Incorporating family members on rounds in the ICU improves communication and satisfaction and shifts the team's time away from family communication events outside of rounds, condensing most of those activities within the rounding structure. Critical care nurses and intensivists were principally satisfied with the process. LEVEL OF EVIDENCE: Therapeutic, level III.